2002
DOI: 10.1021/jm0155704
|View full text |Cite
|
Sign up to set email alerts
|

Rhodacyanine Dyes as Antimalarials. 1. Preliminary Evaluation of Their Activity and Toxicity

Abstract: The rhodacyanine dye MKT-077 (1), a potent antitumor agent, was found to possess strong in vitro activity against Plasmodium falciparum and a low cytotoxicity. Several new rhodacyanine dyes related to 1, containing a variety of linked heterocyclic moieties, were synthesized, and their antimalarial potencies were evaluated. The synthetic rhodacyanines were found to have EC(50) values against P. falciparum in vitro in the range of 4-300 nM. Several compounds in this series have remarkable selective toxicity prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 8 publications
1
56
0
Order By: Relevance
“…Replacement of methyl group as an R 5 substituent by an ethyl group resulted in a 10-fold increase in antiplasmodial potency for 6ab (versus 6aa), but a 2-fold decrease in activity was observed for 6ce (versus 6cc). b-Hydroxyethyl substituent for R 5 group also lead decrease in activity (6pa versus 6pb). It was observed that counter anion (X Ϫ ) affected antiplasmodial properties to some extent (runs 9,11,12).…”
Section: )mentioning
confidence: 96%
See 2 more Smart Citations
“…Replacement of methyl group as an R 5 substituent by an ethyl group resulted in a 10-fold increase in antiplasmodial potency for 6ab (versus 6aa), but a 2-fold decrease in activity was observed for 6ce (versus 6cc). b-Hydroxyethyl substituent for R 5 group also lead decrease in activity (6pa versus 6pb). It was observed that counter anion (X Ϫ ) affected antiplasmodial properties to some extent (runs 9,11,12).…”
Section: )mentioning
confidence: 96%
“…After cooling to ambient temperature, the resulting precipitate was collected by filtration, which was subjected to ion exchange polymer (Amberlyte IRA-400) to give 6cj (53. 5 42) were supplied by the Japanese Cancer Research Resources Bank (JCRB). FM3A cells were maintained in suspension culture at 37°C in a 5% CO 2 atmosphere in plastic bottles containing ES medium (Nissui Pharmaceuticals, Tokyo, Japan) supplemented with 2% heat-inactivated fetal bovine serum (Gibco, NY, U.S.A.).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…24) We expected that DLCs could provide a new class of chemotherapeutics for the treatment of malaria. [25][26][27][28][29] …”
Section: π-Delocalized Lipophilic Cationic Motifmentioning
confidence: 99%
“…In this paper, the rhodacyanines synthesized by our group were categorized into five classes in the following manner: [0, 0], [1,0], and [0, 0, 0] rhodacyanines (classes I to III, respectively), [25][26][27][28] and [0, 0] and [0, 0, 0] azarhodacyanines (classes IV, V, respectively). 29) Dyes in classes I, II, and IV were distinguished by the length of the methine linkage between the heterocyclic A-rings and the rhodanine B-rings.…”
Section: )mentioning
confidence: 99%